The Effect of ERP Implementation on Firm Performance Through Information Technology Capability and Inventory Management During the Covid-19 Pandemic - Zeplin Jiwa Husada Tarigan; Djiantoro Djiantoro (Petra International Journal of Business Studies, 2022)
The Covid-19 pandemic impacts uncertainty in the global economy, with many policy changes set by the government, is trying to prevent the spread of the virus. The company seeks to optimize the use of information technology by using enterprise resource planning. Research using research population are manufacturing companies in East Java that have three years implemented ERP. Data collection was obtained from 85 companies using the purposive sampling technique and analyzing data using structural equation modeling with smartPLS software. The data analysis showed that the ERP system implementation did not directly impact the company's performance. ERP system implementation can improve inventory level control and information technology capabilities. The level of inventory and information technology capabilities owned by the company can impact the company's performance. Information technology capabilities affect inventory management. The indirect impact is that ERP system implementation affects company performance through inventory levels and information technology capabilities. The research contributes to supply chain integration theory to improve company performance on an ongoing basis. Practical contributions for warehouse managers and other functions can take advantage of inventory-level information to improve company performance.